Relación entre la Escala diagnóstica de Moreno y el diagnóstico clínico de neumonía en pacientes pediátricos hospitalizados, Loreto 2024 - Rodríguez Rivera, Lucía Fernanda Sarita (2025)
Objective: To determine the relation between the Moreno Diagnostic Scale and the clinical diagnosis of pneumonia in hospitalized pediatric patients during the year 2024. Method: Observational, descriptive, cross-sectional, and retrospective study conducted at the Regional Hospital of Loreto with a total sample of 73 cases. A clinical and epidemiological data form and the Moreno Diagnostic Scale were used for data collection; descriptive analysis of categorical and nominal variables was performed using frequencies and percentage measurements, and the relation between the Moreno Diagnostic Scale and clinical pneumonia diagnoses was evaluated using Chi-square. Results: It was found that in the study, the 38.3% were older infants, 54.8% were male, and 86% came from the province of Maynas; 82.2% presented subcostal retraction and 72.6% presented tachypnea. The Moreno Diagnostic Scale detailed that 46.6% presented a temperature ≥ 39°C, 68.5% were aged ≥ 9 months, 50.7% had a neutrophil count ≥ 8000/mm3; and 75.3% presented interstitial and/or peribronchial infiltrate. Crossing the scale with the clinical diagnosis; the Chi-square yielded a p-value = 0.021. Conclusion: The Moreno Diagnostic Scale presents an acceptable level of concordance with the clinical diagnosis; therefore, it is considered a useful tool to support the etiological diagnosis of patients diagnosed with pneumonia in the hospital setting.